Keanekaragaman Serangga Permukaan Tanah Pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq) di Kecamatan Kampar Kiri Tengah Kabupaten Kampar Sebagai Rancangan Booklet SMA Kelas X Pada Materi Keanekaragaman Hayati - Desi Lesmini Br. Harahap; Fitra Suzanti; Suwondo Suwondo (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to determine the diversity of ground insects in oil palm plantations in Kampar Kiri Tengah District, Kampar Regency. This research was carried out for 3 months from February to May 2025. This study consists of two stages, namely data collection of ground insects and booklet design. The method of collecting ground insect data was "purposive sampling", sampling using a pitfall trap (trap). The samples obtained were identified in Biology, FKIP UNRI and analyzed using the Shannon-Wiener species diversity index. The results of the study of ground insects obtained 487 individuals belonging to 12 species and 4 orders consisting of Harpalus rufipes, Staphylinus caesarius, Entomobrya unostrigata, Isotomurus palustris, Anoplolepis gracilipes, Dolichoderus thoracicus, Formica rufa, Labidus raedator, Lasius niger, Monomorium minimum, Solenopsis fugax, Gryllus bimaculatus. The diversity index of ground insects at station I was 2.28 (moderate), station II was 2.22 (moderate) and station III was 2.31 (moderate). The physical-chemical factors in oil palm plantations have a soil pH of 6.33-7, temperature of 32.7-34.6 ° C, air humidity of 59-63% and light intensity of 157-224 lux. The data from the results of this study have the potential to be used as a booklet design on biodiversity material.